Query Optimization Using Fuzzy Logic in Integrated Database - Susana Susana; Suharjito Suharjito (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Query optimization in integrated database can’t be separated from data processing method.  In order to have faster query response time, a method to optimize queries is required.  One of many methods that can be used for query optimization is using fuzzy logic with Tsukamoto inference system.  Value set on each variable is defined membership functions and Tsukamoto inference system used in determining these rules or the terms of query results, then apply it into query method or query line structure.  The application of fuzzy logic inference systems with Tsukamoto can accelerate query response time, and will have more significant difference when the amount of selected data is greater.